2018
DOI: 10.1111/een.12508
|View full text |Cite
|
Sign up to set email alerts
|

Resource density regulates the foraging investment in higher termite species

Abstract: 1. Resource density can regulate the area that animals use. At low resource density, there is a conflict in terms of balance between costs of foraging and benefits acquired. The foraging of the higher termite Nasutitermes aff. coxipoensis consists of searching throughout trails and a building galleries phase.2. In this study, a manipulative field experiment was used to test the hypothesis that colonies of N. aff. coxipoensis forage towards a more profitable balance between the establishment of trails and galle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Branching patterns further constrain the spatial positioning of higher‐order branches (Robinson et al., 2003). In animal systems, a parallel to such constraints may be the use of established paths or tunnels in ant and termite foraging that lead individuals to the most profitable foraging areas (Almeida et al., 2018; Traniello, 1989). Beyond the constraints of shared spatial origin, plant roots are expected to follow the ideal free distribution in the absence of competitors, minimising intraplant competition and maximising resource uptake efficiency (McNickle & Brown, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Branching patterns further constrain the spatial positioning of higher‐order branches (Robinson et al., 2003). In animal systems, a parallel to such constraints may be the use of established paths or tunnels in ant and termite foraging that lead individuals to the most profitable foraging areas (Almeida et al., 2018; Traniello, 1989). Beyond the constraints of shared spatial origin, plant roots are expected to follow the ideal free distribution in the absence of competitors, minimising intraplant competition and maximising resource uptake efficiency (McNickle & Brown, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, C. formosanus changes its recruiting behavior, depending on the quality and amount of food (WALLER; LA FAGE, 1987). Almeida et al (2018) showed that the foraging behavior of Nasutitermes aff. coxipoensis is regulated by food resource availability in experiments carried out in the Brazilian Northeastern region.…”
Section: Discussionmentioning
confidence: 99%
“…Communication among nestmates is widespread in ants and other social insects (Beckers et al 1989;Hölldobler and Wilson 1990;Jarau and Hrncir 2009;Almeida et al 2018;Glaser and Grüter 2018;Grüter and Czaczkes 2019). It allows the members of a colony to exchange information about their environment, such as the locations of food sources or the presence of predators and competitors (Kendal et al 2004;Dawson and Chittka 2014;Lanan 2014).…”
Section: Introductionmentioning
confidence: 99%